Purchase Decisions Smartphone Device and Factors Affecting on Depok City West Java - Nofiyanti, Rina (Inovbiz: Jurnal Inovasi Bisnis, 2024)
Purchase decision is a process where when consumers choose a product, consumers often consider various things. Smartphones are products that are loaded with technology that is dynamic in its development and requires manufacturers to understand consumer behavior in making purchases. This study aims to analyze whether partially and simultaneously perception of price, brand image and product quality affect purchasing decisions with the product used is a Samsung smartphone. Type of research is quantitative,  population is the people of the city of Depok, West Java, who have or are currently using a Samsung smartphone. Sampling using non-probability sampling with purposive sampling technique. Data collection using an online questionnaire instrument, and can be collected 207 respondents on October 2023. The data analysis phase is the validity, reliability, and classical assumption test. The data analysis technique used multiple linear regression, coefficient of determination and hypothesis testing with SPSS. The partial results showed that all variables had a significant positive effect on purchasing decisions, with the greatest influence on Brand Image and Product Quality.  Simultaneously all variables are able to have a direct influence on purchasing decisions, the closeness of the influence of the independent variables on the dependent variable simultaneously can be said strong because  reaches about 70 percent, while the rest can  influenced by other factors outside the study.